Surface functionalization of microscaffolds produced by high-resolution 3D printing: A new layer of freedom - Oliver Kopinski-Grünwald; Stephan Schandl; Jegor Gusev; Ourania Evangelia Chamalaki; Aleksandr Ovsianikov (Materials Today Bio)
Scaffolded-spheroids represent novel building blocks for bottom-up tissue assembly, allowing to produce constructs with high initial cell density. Previously, we demonstrated the successful differentiation of such building blocks, produced from immortalized human adipose-derived stem cells, towards different phenotypes, and the possibility of creating macro-sized tissue-like constructs in vitro. The culture of cells in vitro depends on the supply of various nutrients and biomolecules, such as growth factors, usually supplemented in the culture medium. Another means for growth factor delivery (in vitro and in vivo) is the release from the scaffold to alter the biological response of surrounding cells (e.g. by release of VEGF).1 As a proof of concept for this approach, we sought to biofunctionalize the surface of the microscaffolds with heparin as a ''universal linker'' that would allow binding a variety of growth factors/biomolecules. An aminolysis step in an organic solvent made it possible to generate a hydrophilic and charged surface. The backbone of the amine, as well as reaction conditions, led to an adjustable surface modification. The amount of heparin on the surface was increased with an ethylene glycol-based diamine backbone and varied between 8 and 40 ng per microscaffold. Choosing a suitable linker allows easy adjustment of the loading of VEGF and other heparin-binding proteins. Initial results indicated that up to 5 ng VEGF could be loaded per microscaffold, generating a steady VEGF release for 16 days. We report an easy-to-perform, scalable surface modification approach of polyester-based resin that leads to adjustable surface concentrations of heparin. The successful surface aminolysis opens the route to various modifications and broadens the spectrum of biomolecules which can be delivered.